308. Re-purposing Beta-lactam Antibiotics as Fluoroquinolone Sparing Stepdown Therapy for the Treatment of Enterobacteriales Bloodstream Infections. (31st December 2020) - Davis, Matthew; McManus, Dayna; Ruggero, Michael; Topal, Jeffrey E
Abstract: Background: Oral antimicrobial therapy for Enterobacteriales bloodstream infection (EB-BSI) is advantageous to reduce the risk of central line complications, cost of care, and length of stay. Fluoroquinolones (FQ) given their high bioavailability have been utilized as the standard for stepdown therapy (SDT) for EB-BSI. Given the recent increased warnings around FQ use including Clostridioides difficile infection (CDI) and the increasing FQ resistance alternative oral options for treatment are warranted. Recent literature has suggested beta-lactams (BLM) may be an option for EB-BSI. To enhance the antimicrobial stewardship goal of reducing FQ use, our team began recommending de-escalation to a BLM for EB-BSI and the objective of this study is to evaluate the outcomes of this approach. Methods: This study was a retrospective chart review of patients with EB-BSI due to ceftriaxone sensitive monomicrobial E. coli, Klebsiella spp., or P. mirabilis who received a BLM or a FQ as SDT. Patients were excluded if < 18 years of age; pregnant; ANC < 1000 cells/µL; had endocarditis, a bone/joint, or a CNS infection; discharged to hospice or expired prior to discharge; anaphylactic BLM allergy; or prior kidney transplant. SDT was defined as a switch to a definitive oral antibiotic after empiric IV therapy. The primary outcome was clinical cure defined as completion of therapy without signs of infection (increase in WBC > 2000 cells/mL if WBC was ≥ 12, 000 cells/mL, fever (>38°C), or change in antibiotic due to failure). Secondary outcomes included 30 day re-admission rates, reinfection rate defined as positive culture within 30 days of completion of therapy, antibiotic associated adverse events defined as side effects leading to discontinuation and/or CDI within 90 days from start of treatment. Results: A total of 159 patients were included in the study (Figure 1). The BLM patients had a higher median age (78 vs 72, p=0.008), higher median PITT bacteremia score (2 vs 1, p=0.037), were less likely to be immunosuppressed (9% vs 25%, p=0.045), and had shorter median duration of therapy (13 vs 14, p=0.034). There was no difference in the primary or secondary outcomes (Table 2). Conclusion: BLM may enhance stewardship efforts as a FQ sparing option for treatment of EB-BSI; however, prospective studies in this area are warranted. Disclosures: All Authors : No reported disclosures